Advanced Biomaterials for Regulating Polarization of Macrophages in Wound Healing. (5th December 2021) - Mao, Jiayi; Chen, Lu; Cai, Zhengwei; Qian, Shutong; Liu, Zhimo; Zhao, Binfan; Zhang, Yuguang; Sun, Xiaoming; Cui, Wenguo
Abstract: Macrophage immunotherapy is an emerging treatment strategy that modulates the immune system to promote wound healing. The functionality and regeneration of tissue depend on spatially and temporally regulating the biophysical and biochemical microenvironmental with poorly understood mechanisms. Biomaterials are carefully crafted to display and deliver macrophage regulatory signals in a precise and near‐physiological way, serving as powerful artificial microenvironments in which to explore and direct the fate of macrophages. The review starts with discussing the classification and function of macrophages, and then introduces the polarization of macrophages in different microenvironments of conventional wounds and chronic wounds. Recent advances in biomaterials that balance the phenotypes of macrophages in wound healing are emphasized. Finally, looking ahead, the potential ability of biomaterial scaffolds to modulate immune signaling to produce an environment conducive to regeneration is discussed. Abstract : This review begins with a discussion of macrophages and the polarization of macrophages in the different microenvironments of conventional and chronic wounds. Then, recent advances in biomaterials that balance the macrophage phenotype in wound healing are highlighted. Finally, looking ahead, the potential ability of biomaterial scaffolds to modulate immune signaling to produce an environment conducive to regeneration is discussed.